THE RELATIONSHIP OF KNOWLEDGE AND DIET COMPLIANCE WITH BLOOD SUGAR LEVELS IN DIABETES MELLITUS PATIENTS IN THE POLYCLINIC ROYAL PRIMA JAMBI HOSPITAL IN 2023 - Suryani, Dini Dini; Sari.AZ, Winna Kurnia; Mulyati, Sri; Minas Sari, Putri (E-Jurnal Medika Udayana, 2024)
The World Health Organization (WHO) reports that 422 million people globally suffer from DM as of May 2020 and based on this data, Indonesia is ranked fourth with the highest number of DM sufferers after China, India and the United States. Based on the same report, it is estimated that in 2030 there will be 21.3 million DM sufferers in Indonesia. The incidence of DM in Jambi Province in the 2013 Riskesdas results was 1.2%, then increased to 1.4% in 2018. This study aims to determine the relationship between knowledge and dietary compliance with blood sugar levels in diabetes mellitus patients at the Royal Hospital Polyclinic. Prima Jambi City. This research is a quantitative study using cross sectional research. This research was conducted at the Royal Prima Hospital, Jambi City and was carried out in August 2023. The population of this study were outpatients at the Royal Prima Hospital, Jambi City. The sampling technique was taken using an accelerated sampling technique of 85 respondents. Data processing was carried out using univariate and bivariate analysis using the Chi Square test. The research results showed that there was no significant relationship between knowledge and dietary compliance with blood sugar levels at the Royal Prima Hospital, Jambi City. It is hoped that the Royal Prima Hospital will need to provide/create an educational program for DM patients who seek treatment at the Internal Medicine Polyclinic. Keywords: Knowledge. , Diet Compliance. , Blood Sugar Levels. , Diabetes Mellitus.